2017
DOI: 10.1016/s2213-2600(17)30215-1
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of lumacaftor and ivacaftor in patients aged 6–11 years with cystic fibrosis homozygous for F508del-CFTR : a randomised, placebo-controlled phase 3 trial

Abstract: Vertex Pharmaceuticals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
214
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(246 citation statements)
references
References 36 publications
22
214
1
8
Order By: Relevance
“…The safety profile observed was similar to that during prior trials, except for a higher rate of transaminase elevations in these younger patients 19 , 20 . Recommendations for co-administration of lumacaftor-ivacaftor and strong CYP3A inhibitors have been modified to starting at lower than established dose, according to patient’s age, for the first week of treatment to allow for the steady-state induction effect of lumacaftor prior to increasing to the usual recommended daily dose 26 .…”
Section: Safety Evaluationsupporting
confidence: 55%
See 2 more Smart Citations
“…The safety profile observed was similar to that during prior trials, except for a higher rate of transaminase elevations in these younger patients 19 , 20 . Recommendations for co-administration of lumacaftor-ivacaftor and strong CYP3A inhibitors have been modified to starting at lower than established dose, according to patient’s age, for the first week of treatment to allow for the steady-state induction effect of lumacaftor prior to increasing to the usual recommended daily dose 26 .…”
Section: Safety Evaluationsupporting
confidence: 55%
“…An open label study showed no statistically significant increase in ppFEV1, but showed improvement in lung clearance index (LCI), indicating reduction of ventilation inhomogeneity, a sensitive marker of small airways disease 19 . A larger placebo controlled study showed a significant increase in ppFEV1 compared to placebo, though on a similar scale to that in the open-label study, as well as improvement in LCI 20 .…”
Section: Clinical Applications Including Key Efficacy Datamentioning
confidence: 89%
See 1 more Smart Citation
“…Early intervention to minimise the chronic loss of lung function and potentially increase survival are essential, and thus there is a need for early childhood studies of lumacaftor‐ivacaftor. Studies have now been performed in children aged 6–11 years, resulting in change of approval overseas to include children down to age 6 years . In that study, children in the active arm were dosed with lumacaftor 200 mg/ivacaftor 250 mg every 12 h for 24 weeks.…”
Section: Cftr Modulator Therapymentioning
confidence: 99%
“…LCI is said to be a more sensitive measure of lung function than spirometry in reflecting early abnormalities in the smaller airways and is calculated using a multiple‐breathe inert gas washout . In addition to decreases in LCI (which is a positive effect), children in the active group showed decreases in sweat chloride and maintained spirometric lung function where available . Of interest was the observation of increased faecal elastase, suggesting partial restoration of pancreatic function, as has been observed with ivacaftor monotherapy .…”
Section: Cftr Modulator Therapymentioning
confidence: 99%